Pembentukan Kepribadian Positif Anak Sejak Usia Dini - Daviq Chairilsyah (Jurnal Educhild : Pendidikan dan Sosial, 2012)
Currently the development of civilization in Indonesia is stilltinged with moral behaviors are negative. Increasing number ofcases of corruption, violence and criminal cases shows the amoralbehavior. This behavior is the result of one's personality.Formation of personality has been started since the golden era(Golden Age) that is 0-6 years, or during early childhoodeducation. Therefore, this paper reminds us of the need forpersonality of education both at home and at school to be moreintensified. Some methods that can be done by parents andteachers of early childhood educators in order to make a positivepersonal foundation in children can be done with several methodsor means, among other things: teach a child with a concreteexample, do not get enough positive advise, teach child to controlhis emotions, punishment and reward program implemented,introducing God and religion since childhood, became a model ofpositive personal, social supervise the child, watching thespectacle of children and internet technology to supervise children.Expected with these methods may be a reference for parents andearly childhood teachers in early childhood formatting who havepositive personality traits.Kata kunci: Kepribadian, anak usia dini